2015
DOI: 10.1037/bne0000058
|View full text |Cite
|
Sign up to set email alerts
|

A sex difference in circadian food-anticipatory rhythms in mice: Interaction with dopamine D1 receptor knockout.

Abstract: Restricted daily feeding schedules induce circadian rhythms of food-anticipatory activity (FAA) in mice and other species. The entrainment pathway(s) and location(s) of circadian oscillators driving these rhythms have not been definitively established. An important role for dopamine signaling and the dorsal striatum is suggested by a confluence of observations, including shifting of FAA rhythms by dopamine receptor agonists and attenuation by antagonists and D1 receptor knockout (D1R KO). The dopamine reward s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…A study from our laboratory of FAA induced by scheduled palatable meals showed that males expressed moderate FAA in response to timed delivery of fatty meals whereas females did not [ 8 ]. More recently, sex differences in FAA to time restricted feeding (negative energy balance conditions) were independently confirmed in two laboratories [ 9 , 10 ]. Michalik and colleagues found an additive effect of deletion of dopamine receptor 1 and female sex on weakening FAA [ 10 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study from our laboratory of FAA induced by scheduled palatable meals showed that males expressed moderate FAA in response to timed delivery of fatty meals whereas females did not [ 8 ]. More recently, sex differences in FAA to time restricted feeding (negative energy balance conditions) were independently confirmed in two laboratories [ 9 , 10 ]. Michalik and colleagues found an additive effect of deletion of dopamine receptor 1 and female sex on weakening FAA [ 10 ].…”
Section: Discussionmentioning
confidence: 97%
“…A sexual dimorphism in FAA could help to indicate the underlying neuronal circuitry behind the food entrained oscillator(s) given that the male and female brain show only a handful of anatomical differences [ 7 ]. Recently, evidence for biological sex differences in circadian entrainment to scheduled feeding has emerged [ 8 10 ]. In all of these studies, female mice showed a blunted behavioral response to scheduled feeding as compared to males, which showed higher amplitudes of FAA and more rapid entrainment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, FAA was attenuated when the core of the nucleus accumbens was chemically lesioned in rats (Mendoza et al, 2005b ). In addition, FAA was attenuated by inhibition of dopaminergic signaling via treatment with D1 or D2 receptor antagonists (Liu et al, 2012 ) and in D1 receptor knockout mice (Gallardo et al, 2014 ; Michalik et al, 2015 ). It has also been reported that mu-opioid receptor knockout mice display attenuated FAA when feeding is restricted to 3 h during the night (Kas et al, 2004 ), suggesting that endogenous opioids influence the robustness of FAA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that dopamine and opioids, which are important components of the reward pathway, regulate the robustness of FAA (Kas et al, 2004 ; Mendoza and Challet, 2014 ). FAA is attenuated in D1 receptor, but not D2 receptor, knockout mice (Gallardo et al, 2014 ; Michalik et al, 2015 ). Systemic pre-treatment (before the onset of food) with D1 and D2 receptor antagonists attenuated FAA in ICR mice (Liu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that FAA is regulated by a self-sustaining circadian oscillator or oscillators outside the SCN (Figure 3.1), the food entrainable oscillator(s) (FEO) (Mistlberger, 1994;Stephan, 2002). Despite the great number of studies on different central and peripheral structures, the anatomical locus of the FEO is still unknown (reviewed in Davidson, 2009;Mistlberger, 2011;Patton and Mistlberger, 2013 (Gallardo et al, 2014;Michalik et al, 2015). Failure to identify a single structure indicate that the FEO may be a network of widespread oscillators that together mediate food entrainment.…”
Section: Introductionmentioning
confidence: 99%